2020
DOI: 10.1002/lno.11436
|View full text |Cite
|
Sign up to set email alerts
|

Time series assessment of Thaumarchaeota ecotypes in Monterey Bay reveals the importance of water column position in predicting distribution–environment relationships

Abstract: Nitrification plays a key role in marine ecosystems where Thaumarchaeota are thought to be responsible for most of the ammonia oxidation in the water column. Over a 2‐yr, near‐monthly time series at two sites in Monterey Bay we observed repeatable seasonal and depth‐based patterns of Thaumarchaeota ecotype abundance that highlighted a clear delineation between populations in shallow euphotic (< 50 m) vs. deeper mesopelagic (60–500 m) depths. Euphotic depths show greater seasonality and influence from light, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 63 publications
7
13
1
Order By: Relevance
“…GALMSS analysis indicates that Thaumarchaeota was the microbial group with the greater percentage of predictability associated with its spatial and temporal variability (Table 1), and with all the other variables (oxygen, nitrate, ammonium and nitrate), associated with substrates and products of nitrification. In general, these results support a recent report considering the water column position (euphotic, 50 m, and deeper waters 60 -500 m) and other factors such as hydrographic explanatory variables, including oxygen, nitrite and ammonium Thaumarchaeota contribution to total microbial community (iTag-16S rRNA) variability in the Monterey Bay coastal time series (Tolar et al, 2020). However, in the case of the time series off Concepción the Thaumarchaeota depth distribution is resolved within a shallow water column depth (92 m depth).…”
Section: The Spatiotemporal Distribution Of Thaumarchaeota Cell Abundsupporting
confidence: 90%
See 4 more Smart Citations
“…GALMSS analysis indicates that Thaumarchaeota was the microbial group with the greater percentage of predictability associated with its spatial and temporal variability (Table 1), and with all the other variables (oxygen, nitrate, ammonium and nitrate), associated with substrates and products of nitrification. In general, these results support a recent report considering the water column position (euphotic, 50 m, and deeper waters 60 -500 m) and other factors such as hydrographic explanatory variables, including oxygen, nitrite and ammonium Thaumarchaeota contribution to total microbial community (iTag-16S rRNA) variability in the Monterey Bay coastal time series (Tolar et al, 2020). However, in the case of the time series off Concepción the Thaumarchaeota depth distribution is resolved within a shallow water column depth (92 m depth).…”
Section: The Spatiotemporal Distribution Of Thaumarchaeota Cell Abundsupporting
confidence: 90%
“…AOA in the study area were found to be associated to the candidate order Nitrosopumilales (Stieglmeier et al, 2014), and to other ecotypes, i.e., Water Column Surface clade (WCA) with one culture Candidate Nitrosopelagicus brevis and Water Column Deep clades (WCB), as in other coastal marine time series (e.g., Beman et al, 2008;Santoro et al, 2010Santoro et al, , 2015Reji et al, 2019;Tolar et al, 2020). The ammonia-oxidizing assemblages were predominantly characterized by N. maritimus-like followed by WCA amoA reaching higher abundances during winter, whereas the deep WCB amoA ecotype showing maxima during summer at the bottom.…”
Section: Contribution Of Ammonia Oxidizing Archaea Ecotypes In a Reprmentioning
confidence: 85%
See 3 more Smart Citations